Optimalisasi Biaya Transportasi Pendistribusian Pasir Menggunakan Model Transportasi Metode Steppingstone (Studi Kasus: Tangkahan Pasir Syawal) - Amelia, Aida; Dalimunthe, Juniati Suristiani; Pasaribu, Monica; Ritonga, Reza Febrianti; Pohan, Tiara (Indo-MathEdu Intellectuals Journal, 2024)
Tangkahan Pasir Syawal is the largest mining or sand excavation business in Gunung Maria Hamlet, Janji Village, West Bilah District, Labuhanbatu Regency. This research aims to determine the optimization of transportation costs in sand distribution. To obtain the objectives of this research, data collection was carried out through direct interviews, while data analysis used the Vogel's Approximation Method (VAM) to determine the initial solution and to determine the optimal solution using the Stepping Stone method. From the research results, an initial solution of Rp. 6.310.000 and the optimal solution is Rp. 6.310.000. Meanwhile, transportation costs from Tangkahan Pasir Syawal before optimization were carried out were Rp. 9.425.000. This shows that Tangkahan Pasir Syawal can optimize transportation costs for sand distribution in November 2023 with cost savings of Rp. 3.115.000 or 4%.